An in vitro tumor recurrence model based on platinum-resistant colon cancer cells as a research tool for studying cancer cell dormancy - Alisa Morshneva; Olga Gnedina; Maria Igotti (PLoS ONE, 2025)
Modeling cancer recurrence and associated conditions such as cancer cell dormancy remains a significant challenge in cancer research. We developed a novel in vitro model based on platinum-resistant tumor cells treated with a platinum drug, in which cells progress through all stages of recurrence within 30–40 days post-exposure. Our results demonstrate that treatment of platinum-resistant colorectal cancer cells with oxaliplatin enriches the population with quiescent, dormant cells arrested in the G0/G1 phase. These cells exhibit increased autophagy, elevated expression of stem cell markers, reduced reactive oxygen species (ROS) levels, and heightened resistance to chemotherapy. A key advantage of our model is the high survival rate of residual cells, enabling the maintenance of a large cell population. This facilitates the application of conventional research techniques that are often limited in other recurrence models due to the small size of residual populations. Overall, this model provides opportunities for a wide range of further research for studying specific recurrence- and dormancy-associated signaling pathways and for identifying novel therapeutic targets for preventing tumor recurrence.